Acute Hypertensive Retinochoroidopathy Secondary to an Anti-cancer Drug (apatinib): The First Case Report - Yao, Bangtao; Liu, Gang; Wang, Bei; Cao, Qian (Frontiers in Medicine, 2021)
Background: Acute hypertensive retinochoroidopathy is a rare, severe ocular disease, characterized by retinal and choroidal ischaemia. Untreated cases are associated with high mortality and poor visual outcomes. Patients subjected to treatment with the anti-neoplasic drug apatinib may trigger this disease. The purpose of this article is to describe in detail an acute hypertensive retinochoroidopathy in a young Chinese woman treated with apatinib. Case presentation: A 40-year-old young Chinese woman presented a sudden but painless reduction of visual acuity in both eyes. She was previously diagnosed with gastric cancer and metastatic ovarian adenocarcinoma. The treatment consisted radical gastrectomy, transabdominal hysterectomy, bilateral adnexectomy, and 250 mg oral apatinib per day. After 58 days of apatinib administration, the patient immediately sought consult for a sudden decrease in vision. Her blood pressure was 208/136 mmHg and, based on the clinical manifestations, the patient was diagnosed with acute hypertensive retinochoroidopathy. Conclusions: This is the first case report of an apatinib-related acute hypertensive retinochoroidopathy diagnosed using fundal photograph, fundus fluorescein angiography, and spectral-domain optical coherence tomography simultaneously. It is crucial to develop a suitable strategy for management and prevention of this adverse event.